RELATIONSHIP BETWEEN THE RESPONSIBILITY OF A NOTARY ON LEAVE AND THE REPLACEMENT NOTARY - Maulida, Fitria; Faisal, Achmad (JILPR Journal Indonesia Law and Policy Review, 2025)
The appointment of a substitute notary during the notary's leave period is a provision regulated in Law Number 30 of 2004 concerning the Position of Notary as amended by Law Number 2 of 2014 (UUJN). This provision is intended to ensure the continuity of notarial services legally and uninterruptedly. However, in its implementation, the legal relationship between a notary on leave and a substitute notary often causes ambiguity, especially regarding the limits of authority, forms of responsibility, and legal consequences for errors that may occur during the replacement period. First Research Results: The legal relationship between a notary on leave and a substitute notary is based on UUJN. The main focus of the discussion includes the mechanism for appointing a substitute notary by the Regional Supervisory Board, the form of legal relationship established between the two parties, and the limits of the authority of the substitute notary in carrying out his/her duties. In this case, it is emphasized that the relationship between a notary on leave and a substitute notary is not a command or subordinate relationship, but rather a functional relationship that is individual and stands alone in terms of legal responsibility. Second: Specifically the form of responsibility of the substitute notary during the replacement period, especially if there is an error or negligence in making the deed. The substitute notary is fully responsible for every deed made during his/her term of office, without being able to transfer the responsibility to the notary he/she replaces. The responsibility covers three legal aspects, namely civil responsibility for losses incurred by the parties, criminal responsibility if there is an element of violation of the law or forgery, and administrative responsibility which can be in the form of reprimands, warnings, to temporary suspension. This discussion also describes the factors causing errors, starting from personal aspects such as lack of caution, to structural aspects such as weak supervision.